2021
DOI: 10.1002/elsa.202100180
|View full text |Cite
|
Sign up to set email alerts
|

Functional activity of peptide ion channels in tethered bilayer lipid membranes: Review

Abstract: Ion transport across biomembranes plays a major role in living cells. This fundamental function is normally carried out by molecules with both a hydrophobic and a hydrophilic side (amphiphilic molecules), which aggregate within the membrane forming a hydrophilic pore (the ion channel) permitting the selective translocation of permeant ions. Countless papers report the conformation of these ion channels in lipid vesicles using several techniques, such as circular dichroism and solid‐state NMR spectroscopies. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 227 publications
(553 reference statements)
0
2
0
Order By: Relevance
“…The latter case is depicted in Figure 5, with the tether being a polyoxyethylene hydrophilic chain modified on one end with thiol functionality for covalent attachment to metal (gold). The various modes of s-PLB formation are described in more detail in several publications [134,135,152,154] and are brilliantly summarized in the review work [158]. Apart from their stability, the s-PLBs also present another important advantage, which cannot be obtained with the free-standing PLB or patch-clamp technique.…”
Section: Solid-supported and Tethered-lipid Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter case is depicted in Figure 5, with the tether being a polyoxyethylene hydrophilic chain modified on one end with thiol functionality for covalent attachment to metal (gold). The various modes of s-PLB formation are described in more detail in several publications [134,135,152,154] and are brilliantly summarized in the review work [158]. Apart from their stability, the s-PLBs also present another important advantage, which cannot be obtained with the free-standing PLB or patch-clamp technique.…”
Section: Solid-supported and Tethered-lipid Membranesmentioning
confidence: 99%
“…We think that the use of such model membranes deposited on electrodes can greatly enlarge the information gathered with free-standing planar bilayer membranes. Due to their stability, s-PLBs allow for screening of a large library of ionic species, inhibitors/activators, and other molecules affecting the channel activity in a single set of experiments, using the same s-PLB [158,168]. Successful application of s-PLBs may facilitate studies of mitochondrial potassium channels.…”
Section: Solid-supported and Tethered-lipid Membranesmentioning
confidence: 99%
“…EIS has been the popular technique of choice used to test tBLM formation from different lipid compositions mimicking bacterial membrane [8], yeast cell membrane [9] and mammalian cell membrane [10]. EIS based tBLM studies are also employed to understand the interaction of lipid bilayer with membrane proteins [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…EIS has been the popular technique of choic used to test tBLM formation from different lipid compositions mimicking bacterial mem brane [8], yeast cell membrane [9] and mammalian cell membrane [10]. EIS based tBLM studies are also employed to understand the interaction of lipid bilayer with membran proteins [11][12][13][14]. tBLMs have been found to have stable insulating membranes for longer durations The study by Vockenroth [15] shows that tBLMs were observed to have stable electrically insulating membranes for as long as three months.…”
Section: Introductionmentioning
confidence: 99%